(untitled) (Anwer Khan Modern Medical College Journal, 2017)
Foreign body aspiration most commonly affects young children, with respiratory symptoms such as wheeze and cough after a choking episode. A careful history and clinical examination can identify those children that need additional investigation including bronchoscopy. However foreign body aspiration can mimic other conditions. The link between choking and subsequent symptoms may not be made by parents. We present a case with a delay in diagnosis, and discuss the appropriate management of suspected foreign body aspiration. Anwer Khan Modern Medical College Journal Vol. 6, No. 2: July 2015, P 47-49